Natural Abundance Radiocarbon Studies of Dissolved Organic Carbon (DOC) in the Marine Environment - de Jesus, Roman P. (University of California, San Diego, 2008)
Marine dissolved organic carbon (DOC), an active reservoir in the global carbon cycle, has an average age of 6000 years and is comprised of biochemicals which may or may not cycle on different time scales. The primary objective of this thesis is to investigate the relationship between radiocarbon (14C) signature and chemical composition of various fractions within DOC. Specifically, this thesis was designed to provide an analytical framework to explicitly explore the relationship between DOC molecular weight, chemical composition, and reactivity. Chapter 2 describes spatial and temporal total organic carbon (TOC) concentration gradients in 2005 from the California Cooperative Fisheries Oceanic Cooperative (CalCOFI) region, which is the main study area for this thesis. Chapter 3 describes a novel solid phase extraction (SPE) method and reports the chemical and isotopic characteristics of fractionated DOC components based on their solubility. These fractions are compared to DOC isolated by the widely applied UF techniques and the results indicate that chemical composition and 14C content were related. Using compound specific isotope analysis (CSIA) of sugars and lipids, Chapter 4 shows that both SPE DOC and UDOC contain specific compounds with similar chemical and isotopic characteristics and residence times. In Chapter 5, CSIA was applied to SPE samples collected from the Delaware River and Estuary and the terrestrially influenced Eel River Margin to examine whether riverine DOC inputs contribute specific compounds or common components to the coastal ocean. Finally, the final chapter discusses the implications and significance of these results for marine DOC cycling.